2002
DOI: 10.1073/pnas.172198599
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose-mediated transcriptional regulation of sucrose symporter activity in the phloem

Abstract: A proton-sucrose symporter mediates the key step in carbon export from leaves of most plants. Sucrose transport activity and steady-state mRNA levels of BvSUT1, a sugar beet leaf sucrose symporter, are negatively regulated specifically by sucrose. Results reported here show that BvSUT1 mRNA was localized to companion cells of the leaf's vascular system, which supports its role in the systemic distribution of photoassimilate. Immunoblot analysis showed that decreased transport activity was caused by a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
168
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(186 citation statements)
references
References 26 publications
17
168
0
1
Order By: Relevance
“…A construct in which CoYMVp was fused to AtSUC2 complementary DNA (cDNA) was shown to rescue the Atsuc2-4 -/-knockout mutation (Srivastava et al, 2009b). Both BvSUT1 from sugar beet (Beta vulgaris; Vaughn et al, 2002) and AtSUC2 (Osuna et al, 2007) are suppressed by high Suc levels. We previously suggested that the modified fine-tuning of exotic promoters, such as CoYMVp, compared to AtSUC2p, could benefit plant growth by maintaining high AtSUC2 expression under conditions where it is otherwise repressed (Srivastava et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…A construct in which CoYMVp was fused to AtSUC2 complementary DNA (cDNA) was shown to rescue the Atsuc2-4 -/-knockout mutation (Srivastava et al, 2009b). Both BvSUT1 from sugar beet (Beta vulgaris; Vaughn et al, 2002) and AtSUC2 (Osuna et al, 2007) are suppressed by high Suc levels. We previously suggested that the modified fine-tuning of exotic promoters, such as CoYMVp, compared to AtSUC2p, could benefit plant growth by maintaining high AtSUC2 expression under conditions where it is otherwise repressed (Srivastava et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…For Linking powered by eXtyles example strong feedbacks between sugar concentration and sugar loading at the source have been found to exist (e.g. Vaughn et al, 2002). A steady state model approach cannot explicitly incorporate these feedbacks.…”
Section: Limitations and Advantages Of The Modelling Approach Presentedmentioning
confidence: 99%
“…Biochemical studies have shown Suc transport activity for numerous dicot as well as monocot SUTs (for recent reviews, see Aoki et al, 2003;Kü hn, 2003;Lalonde et al, 2004;Sauer, 2007). In multiple plants, it has been shown that SUT RNA and/or protein abundance is regulated by Suc (Chiou and Bush, 1998;Aoki et al, 1999;Matsukura et al, 2000;Vaughn et al, 2002;Ransom-Hodgkins et al, 2003), but the genes that control SUT expression have not been identified.…”
Section: Sutsmentioning
confidence: 99%